2005
DOI: 10.1681/asn.2004070600
|View full text |Cite
|
Sign up to set email alerts
|

Novel Serpinopathy in Rat Kidney and Pancreas Induced by Overexpression of Megsin

Abstract: The intracellular polymerization of abnormal serine protease inhibitors (serpins) results in liver or neuronal cell abnormalities recently identified as "serpinopathies." It was demonstrated in transgenic rats that overexpression of megsin, a recently discovered serpin located in the kidney, produces renal and pancreatic lesions characteristic of serpinopathies. Megsin expression is elevated in a variety of organs, including kidney and pancreas. Periodic acid-Schiff-positive, diastase-resistant intracellular i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…Previous reports by our and other groups have emphasized a pathogenic role of ER stress in glomerular and tubular epithelial injury. 14,17,20,21 Immunohistochemical analysis in this study showed upregulation of the ER chaperones GRP78 and ORP150 in the glomeruli of rats with antiThy1 nephritis. Furthermore, activation of the PERK pathway, a UPR pathway involved in the downregulation of translation, was also detected in the glomeruli of these rats.…”
Section: Discussionsupporting
confidence: 49%
“…Previous reports by our and other groups have emphasized a pathogenic role of ER stress in glomerular and tubular epithelial injury. 14,17,20,21 Immunohistochemical analysis in this study showed upregulation of the ER chaperones GRP78 and ORP150 in the glomeruli of rats with antiThy1 nephritis. Furthermore, activation of the PERK pathway, a UPR pathway involved in the downregulation of translation, was also detected in the glomeruli of these rats.…”
Section: Discussionsupporting
confidence: 49%
“…We have previously observed polymers in COS-7 cells transfected with M a 1 -antitrypsin (E.M. and D.A.L., unpublished results) whereas others have reported the polymerization of the wild-type serpin megsin when expressed at high levels. 28 These results demonstrate that the 2C1 mAb recognizes polymers formed by different disease associated variants of a 1 -antitrypsin, including Z and a range of shutter domain mutants.…”
Section: Resultsmentioning
confidence: 68%
“…Megsin, a mesangial-cell-specific serine protease inhibitor, is known to be induced during the progression of glomerular injury and to participate in the pathogenesis of mesangial nephritis (32). Notably, we found that the G3YR mouse kidneys showed significantly increased expression of megsin in the glomerular cell fraction (Fig.…”
Section: B125-g3mentioning
confidence: 69%